Schooling and its relationship to the social values of students in selected educational institutions in Central and Eastern Visayas - Fabia, Gregoria N. (1987)
This study sought to determine the influence of schooling on the development of the social values of 960 college of commerce and business administration students from two Catholic and two non-Catholic schools in the second semester, 1985-1986. The mean scores on the social values of moral equality and brotherhood were found to increase significantly as students from Catholic schools moved upward in college. The mean scores on the five social values of students from Catholic schools by year level were higher than those for each corresponding year level of students from non-Catholic schools, with very significant differences in the first and second year levels but insignificant differences in the third and fourth year levels. Moral equality is the only social value that increased throughout the college years when all seven personal factors (sex, age, elementary and high schools attended, academic performance, pre-college religious instruction, residence while studying, peer group activity) were controlled.